Hole-mediated photoredox catalysis: tris(p-substituted)biarylaminium radical cations as tunable, precomplexing and potent photooxidants. Issue 6 (3rd March 2021) - Wu, Shangze; Žurauskas, Jonas; Domański, Michał; Hitzfeld, Patrick S.; Butera, Valeria; Scott, Daniel J.; Rehbein, Julia; Kumar, Ajeet; Thyrhaug, Erling; Hauer, Jürgen; Barham, Joshua P.
Abstract : Triarylamines are demonstrated as novel, tunable electroactivated photocatalysts that use dispersion precomplexation to harness the full potential of the visible photon (>4.0 V vs. SCE) in anti-Kasha photo(electro)chemical super-oxidations of arenes. Abstract : As a combination of visible light photoredox catalysis and synthetic organic electrochemistry, electrochemically-mediated photoredox catalysis emerged as a powerful synthetic technique in recent years, overcoming fundamental limitations of electrochemistry and photoredox catalysis in the single electron transfer activation of small organic molecules. Herein we report a tunable class of electroactivated photoredox catalyst, tri( para -substituted)biarylamines, that become superoxidants in their photoexcited states even able to oxidize molecules beyond the solvent window limits of cyclic voltammetry (such as polyfluorobenzene and trifluorotoluene). Furthermore, we demonstrate that precomplexation not only permits the excited state photochemistry of tris( para -substituted)biarylaminium cations to overcome picosecond lifetime, but enables and rationalizes the surprising photochemistry of their higher-order doublet (D n ) excited states, unlocking extremely high oxidative potentials (up to a record-breaking ∼+4.4 V vs . SCE).